Back Cover: Cutting‐edge advancements of nanomaterials for medi‐translatable noninvasive theranostic modalities (View 3/2021). Issue 3 (17th June 2021) - Zhang, Chen; He, Wenxin; Liu, Chenxi; Jiao, Dian; Liu, Zhe
Abstract : In the image of article number 20200144, Zhe Liu and co‐workers have shown: noninvasive theranostic modalities present a best convenience, satisfactory treatment outcome and unprecedented precision, which exactly matches a Chinese phrase as Strike a hill to scare a tiger, and shoot the target over 100 paces away .